2023
DOI: 10.1002/fsn3.3322
|View full text |Cite
|
Sign up to set email alerts
|

Innovative applications and therapeutic potential of oilseeds and their by‐products: An eco‐friendly and sustainable approach

Abstract: The risk of inadequate management of agro‐waste is an emerging challenge. However, the economic relevance of agro‐waste valorization is one of the key strategies to ensure sustainable development. Among the agro‐waste, oilseed waste and its by‐products are usually seen as mass waste after the extraction of oils. Oilseed by‐products especially oilseed cakes are a potential source of protein, fiber, minerals, and antioxidants. Oilseed cakes contain high value‐added bioactive compounds which have great significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…However, the growing human population creates a need for a more logical use of by‐products from the food processing industry (Jozinović et al., 2017 ). Therefore, oilseeds and oils are increasingly common constituents in food products, and as a result, oil plant production is steadily increasing on a global scale (Usman et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the growing human population creates a need for a more logical use of by‐products from the food processing industry (Jozinović et al., 2017 ). Therefore, oilseeds and oils are increasingly common constituents in food products, and as a result, oil plant production is steadily increasing on a global scale (Usman et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…drying, grinding) are also required to remove water and minimise microbial activity, which can reduce subsequent transport costs, minimise food spoilage, and enhance the manufacturing viability of downstream products. Effective drying methods for different by-product types are required to be investigated to ensure to viability of energy and cost consumption [69]. Due to the distributed nature of by-product production, it is not feasible to perform these additional processing steps at the by-product generation site.…”
Section: Logistics and Transportmentioning
confidence: 99%
“…Suitable processing techniques are required to obtain novel products that are safe and allergenfree. Toxicity studies implemented within the development of novel food will be essential to ensure product safety and consumer acceptance [69].…”
Section: Product Safetymentioning
confidence: 99%
“…It is reported that camelina exhibits a lower percentage of essential amino acids in comparison with canola protein [ 9 ], but its composition is well-balanced [ 10 ]. The increasing use of the cold-pressing procedure to obtain the oil is responsible for generating huge amounts of press cakes, which are currently considered a by-product [ 11 ]. The annual production of press cakes and oil industry residues in 2018/2019 was estimated at 600.47 million metric tons [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…To reduce food waste, by-products represent a source of valuable extracts that serve as food additives, including for gluten-free diets. Their high water content and composition, however, makes fresh plant extracts prone to spoilage by microorganisms; in addition, individual phytochemicals tend to have low stability and show vulnerability to oxidation, degradation and hydrolytic cleavage [ 11 , 14 ]. Hence, they should be adequately stabilized before being stored and incorporated into the end product.…”
Section: Introductionmentioning
confidence: 99%